1977
DOI: 10.1002/crat.19770120613
|View full text |Cite
|
Sign up to set email alerts
|

Realstrukturuntersuchungen von hydrothermal auf kleinen Rhomboederflächen gewachsenen Quarzeinkristallen

Abstract: Realstrukturuntersuchungen von hydrothermal auf kleinen Rhomboederflachen gewachsenen Quarzeinkristallen')Es wurden optische, atztechnische und rontgenographische Untersuchungen an Quarzkristallen, die auf Rhomboederkeimen gewachsen waren, durchgefuhrt. Durch Verfarbungsversuche wurde in Ubereinstimmung mit der Literatur festgestellt, dalj sich Aluminiumfremdatome verstarkt in den Wachstumssektor der kleinen Rhomboederflache einbauen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…(2020)-topographseed from major rhombohoclroii 3.2. Seed from the growth sector of the minor rhombohedron Seeds for this case were cut from a crystal, which had previonsly been grown from seeds with surfaces parallel to the minor rhoinbohedral plane (ALTER et al 1977). We have already shown that dislocations arrange a t an angle of approximately 5 degrees with respect to the growth direction, which can clearly be seen in the seed in Figure 2.…”
Section: Seed From the Growth Sector Of The Major Rhombohedronmentioning
confidence: 99%
“…(2020)-topographseed from major rhombohoclroii 3.2. Seed from the growth sector of the minor rhombohedron Seeds for this case were cut from a crystal, which had previonsly been grown from seeds with surfaces parallel to the minor rhoinbohedral plane (ALTER et al 1977). We have already shown that dislocations arrange a t an angle of approximately 5 degrees with respect to the growth direction, which can clearly be seen in the seed in Figure 2.…”
Section: Seed From the Growth Sector Of The Major Rhombohedronmentioning
confidence: 99%